Sejarah, Bentuk dan Makna Arsitektur Gereja GPIB Bethel Bandung - Masmedia Pinem (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
This article attempts to describe the history, together with the characteristic architecture of GPIB Bethel. GPIB is the abbreviation of the ‘Protestant Church in Western Indonesia’. Built in Bandung, in 1948, it is located in Jalan Wastukencana 1, in the Village of Babakan Ciamis, Sub District of Sumur Bandung, City of Bandung. This type of church structure was designed by Schoemaker, a Dutch architect, who combined and syintisized between basic needs, concepts, and values of each genre that came from developed world archictecture in that time. The model was already well-known as an “essential expression” of European Chris-tianity. Exsisted Elements of church was adapted from world development architecture in that era. The elements of mass and figure have been des-cribed as spiritual manifestations of Christianity. There is perhaps an element of art deco its architectural decoration. The church of Bethel is now a building categorized as ‘A’, meaning that it is to be conserved in its models and functions, prohibited by law from any changes to its functions - it is now a legally protected part of the Indonesian legacy. Keywords: Church, History, Type, Architecture, Bandung. Artikel ini ingin menggambarkan sejarah, bentuk, dan arsitektur Gereja GPIB Bethel. GPIB adalah singkatan dari Gereja Protestan di Indonesia bagian Barat, berdiri sejak tahun 1948 dan terletak di Jalan Wastukencana No. 1, Kelurahan Babakan Ciamis, Kecamatan Sumur Bandung, Kotamadya Bandung. Model arsitektur yang didesain oleh Schoemaker seorang arsitek Belanda yang merupakan sintesis dari kebutuhan, konsep, dan nilai-nilai yang dimiliki oleh masing-masing aliran-aliran dalam perkembangan arsitektur dunia sebagai produk arsitektur pada zamannya yang merupakan “essential expression” bagi kekristenan di Eropa. Elemen-elemen yang ada merupakan adaptasi dari pengaruh zaman yang berkembang saat itu. Elemen pada tatanan massa dan ruang serta elemen pelingkup ruang yang dijumpai memiliki makna kerohanian sebagai perwujudan nilai-nilai Kristianitas. Begitu juga elemen-elemen dekoratifnya merupakan suatu produk zaman yang dipengaruhi oleh arsitektur art deco yang sangat berkembang pada zaman itu. Gereja ini adalah termasuk salah satu tipe bangunan yang berkualitas ‘A’ dan telah dikonservasi tanpa perubahan bentuk dan fungsi yang signifikan, sehingga ia termasuk dalam kategori bangunan Cagar Budaya yang dilindungi oleh Undang-Undang. Kata Kunci: Gereja, Sejarang, Bentuk, Arsitektur, Bandung.